KLF4 promotes cisplatin resistance by activating mTORC1 signaling in ovarian cancer - Wanzhen Zhou; Huixian Huang; Yincheng Teng; Rong Hua; Yan Hu; Xiao Li (Discover Oncology)
Abstract Ovarian cancer (OC) is a highly fatal gynecological malignancy worldwide, and cisplatin (CDDP) is commonly used as an initial chemotherapy treatment for OC. Nonetheless, most patients ultimately face recurrence because of resistance to cisplatin. Therefore, it is imperative to investigate the underlying mechanisms of drug resistance in OC. By analyzing differential gene expression using TCGA, GDSC, and GEO public databases, we discovered that increased KLF4 expression is strongly linked to chemotherapy resistance and unfavorable outcomes in OC. Subsequent validation through immunohistochemistry and western blotting confirmed the upregulated KLF4 expression in cisplatin-resistance OC cells lines and tissues. To investigate the function of KLF4, functional experiments were performed both in vitro and in vivo. We observed that knocking down KLF4 impaired cisplatin-resistance of OC. Further mechanism research based on RNA-seq and gene enrichment analysis revealed that interfering KLF4 suppressed the activation of mTORC1 pathway. Finally, rescue experiment demonstrated that using mTORC1 pathway inhibitor could attenuate the cisplatin resistance induced by the overexpression of KLF4. In conclusion, our research indicates that KLF4 promotes cisplatin resistance through the activation of mTORC1 signaling, and proposes that inhibiting KLF4 might serve as a viable therapeutic approach to overcoming drug resistance in ovarian cancer.